Meningkatkan Literasi Melalui Bahan Ajar Tematik Saintifik Berbasis Kearifan Lokal - Nuhyal Ulia; Yulina Ismiyanti; Leli Nisfi Setiana (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2019)
The literacy movement is being carried out by the government nationally in various circles ranging from families, schools and communities. It is also entitled to be felt by all people including street children. For street children literacy culture also needs to be grown because their literacy is still low. This effort was carried out by increasing literacy in "Lotus" street children in the Social Barracks of Demaan Village, Kudus Regency, Central Java. Lack of interest in learning because teaching materials in schools are not easy for them to digest, making them less desirable and a burden on them. Teaching materials that are made thematically presented in the form of reading about local wisdom around them are expected to improve their literacy culture. The PKM is carried out by mentoring educational programs in the form of tutoring and training in improving literacy. In mentoring using teaching materials that have been developed by applying several methods. Like learning methods based on study groups according to age with approaches such as scientific, thematic, tutorial, drill and lecture. while the implementation of literacy training delivered good reading and writing methods. From this PKM activity, it was found that the level of enthusiasm of attendance was very high %80%, literacy ability had experienced an increase of> 10% with a significant.